THE EFFECTIVENESS OF WARM AND COLD COMPRESSES BEFORE INFUSION TO REDUCE PAIN IN CHILDREN AGED 1-6 YEARS - Prameswari, Veryudha Eka; Sa’diyah, Khalimatus; Kusmindarti, Indah (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: Infusion can cause trauma to the child. The purpose of the study was to determine whether there was a difference in the administration of warm compresses and cold compresses to pain after infusion.Method: The research design used is a Quasi Experimental Design with a Post Test Only Non Equivalent Control group design to get a sample of 30 respondents taken by consecutive sampling. The independent variable is warm and cold compresses on pain after infusion in children and the dependent variable is pain intensity after infusion. Data was taken by using observation with Wong Baker Face scale. After collecting the data processing and proceeding with the Wilcoxon rank test statistical test which was carried out using the SPSS program.Result: The results showed 0.000 then p < (0.05), there was a difference between warm compresses and cold compresses before infusion on pain intensity.Conclusion:  Cold compresses are more dominant in reducing heat because they are better able to suppress autonomic responses, while warm compresses cause vasodilation associated with local blood vessel dilation. It is hoped that it can urge nurses to provide direct warm compress therapy and cold compresses to pediatric patients who will be given an infusion as one of the non-pharmacological therapies to reduce pain intensity.